POPULATION STRUCTURE AND REPRODUCTION OF THE RAZOR CLAMS Solen lamarckii (Chenu, 1843) IN THE INTERTIDAL ZONE OF API API VILLAGE WATERS, BENGKALIS REGENCY - Fahmia, Rani; Nasution, Syafruddin; Tanjung, Afrizal (Asian Journal of Aquatic Sciences, 2020)
Razor clam (Solen lamarckii) is a type of pelecypoda that has high economic value on the Api api village waters, Bengkalis Regency. This research aims to study the population structure and reproduction of razor clam. The study was carried out over 2 month period from September to October 2019 at Api api village waters, Bengkalis Regency. Razor clam samples were collected by using a 1 x 1 m2 frame that laid along transect. There were 5 plots and 5 subplots along the transect as replications. The result showed, the population density of razor clams is 3.12 species/m2 in September and 2.88 species/m2 in October 2019. The distribution pattern of razor clams was uniform. While, the most common size of razor clam is the medium size category (40-60 mm) both in September and in October 2019. The average value of gonado somatic index (GSI) was 2.28-8.60%. Histological analysis indicated that maturity gonad stage of razor clam was commonly found in September is maturity gonad stage I (60%), while in October is stage III (40%) and stage IV(30%).